EASEing Students Into College: The Impact of Multidimensional Support for Underprepared Students. (October 2018) - Xu, Di; Solanki, Sabrina; McPartlan, Peter; Sato, Brian
Extensive theoretical literature and qualitative evidence nominate learning communities as a promising strategy to improve persistence and success among at-risk populations, such as students who are academically underprepared for college-level coursework. Yet rigorous quantitative evidence on the impacts of these programs is limited. This paper estimates the causal effects of a first-year STEM learning communities program on both cognitive and noncognitive outcomes at a large public 4-year institution. We use a regression discontinuity design based on the fact that students are assigned to the program if their math SAT score is below a threshold. Our results indicate that program participation increased the academic performance and sense of belonging for students around the cutoff. These results provide compelling evidence that learning communities can support at-risk populations when implemented with a high level of fidelity.